Relationship between Urinary Disorders and Body Mass Index in Women with Polycystic Ovary Syndrome - Anggraeni, Asih; Budihastuti, Uki Retno; Darto, Darto; Laqif, Abdurrahman; Melinawati, Eriana; Insan Ksyatria, Yudhista Ngudi; Wijayanti, Agung Sari; Putrinadia, Aninditya Verinda (Jurnal Kedokteran Brawijaya, 2026)
Early detection and management of obesity in women with polycystic ovary syndrome (PCOS) have been shown to reduce the risk of urinary problems and enhance their overall quality of life. The present study investigates the correlation between urinary disorders and body mass index (BMI) in women diagnosed with PCOS at Dr. Moewardi Regional General Hospital, Surakarta. A retrospective cohort approach was used over a 12-month time frame in both the outpatient clinic and the inpatient ward. The diagnosis of PCOS was made in accordance with the Rotterdam criteria (2003), whereby it is imperative that a woman fulfils two out of the three criteria, established after ruling out other hormonal disorders. Patients were stratified according to their BMI levels and the presence of urinary symptoms. Information on urinary issues, including urgency, frequency, nocturia, stress incontinence, and symptoms during and after urination, was extracted from the medical records. Statistical analysis was conducted to examine the correlation between urinary dysfunction and body mass index. In 54% of patients diagnosed with PCOS, urinary issues were identified. Of these, 63% were classified as obese. The study established that women diagnosed with PCOS who were obese were found to have more than twice the probability of developing urinary dysfunction in comparison to those with a normal weight. The most commonly reported symptoms included urgency and frequency, nocturia, stress incontinence, and post-voiding complaints. The present study demonstrates a significant correlation between urinary dysfunction and obesity in women diagnosed with PCOS.